2018
DOI: 10.1161/circulationaha.118.033348
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blood Pressure Measurements With Peripheral Artery Disease Events

Abstract: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00000542.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 39 publications
1
36
0
3
Order By: Relevance
“…On-treatment observational studies have shown associations among lower DBP and higher rates of adverse cardiac ischemic events, particularly in populations with established coronary artery disease [1][2][3][4]12 . For example, a secondary observational reanalysis of 22,576 patients with hypertension and coronary artery disease enrolled in the International Verapamil-Trandolapril Study (INVEST) showed that patients with an achieved mean DBP of <60 mm Hg had a higher incidence of cardiovascular events and death compared with their counterparts who had a higher mean achieved DBP 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On-treatment observational studies have shown associations among lower DBP and higher rates of adverse cardiac ischemic events, particularly in populations with established coronary artery disease [1][2][3][4]12 . For example, a secondary observational reanalysis of 22,576 patients with hypertension and coronary artery disease enrolled in the International Verapamil-Trandolapril Study (INVEST) showed that patients with an achieved mean DBP of <60 mm Hg had a higher incidence of cardiovascular events and death compared with their counterparts who had a higher mean achieved DBP 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Coronary perfusion primarily occurs during diastole, and intensive systolic blood pressure (SBP) lowering often leads to diastolic blood pressure (DBP) lowering. In observational on-treatment analyses, lower DBP is associated with an increased risk of cardiovascular disease events and death in patients at higher risk for cardiovascular events [1][2][3][4] . Concern related to DBP lowering may be of particular relevance among patients with chronic kidney disease (CKD), given the higher prevalence of elevated SBP and lower DBP in that population, due in part to known associations of CKD with premature vascular aging and vascular stiffness 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, all patients with arterial hypertension benefit from a reduction in blood pressure [13], and patients with PAD ( = high-risk patients) in particular have an improved cardiovascular prognosis. In patients with PAD, RR < 120 mmHg and > 160 mmHg result in more leg events [14].…”
Section: Therapy Of Hypertension In Patients With Padmentioning
confidence: 99%
“…Non-high-density lipoprotein cholesterol (non-HDL-c) includes both LDL-c and remnant cholesterol and has a stronger association with cardiovascular outcomes in comparison with LDL-c 9. Hypertension is associated with an increased risk of PAD and MALE in the general population 10 11. In patients with PAD, however, it has been suggested that lowering blood pressure below a critical level may worsen PAD symptoms and progression by decreasing peripheral perfusion 12.…”
Section: Introductionmentioning
confidence: 99%